Representações sociais da obesidade e do processo de emagrecimento em pessoas que realizaram cirurgia bariátrica - LIMA, Taiane Freitas (2018)
Obesity has been increasing globalization, and is a condition that may reflect negatively on the physical and mental health of individuals. Social prejudice, such as physical and emotional limitations in weight loss attempts, are the other reasons, the factors that lead to bariatric surgery as a form of obesity treatment are important. Thus, this study was seen to be social representatives and the obesity and process of weight loss in people who performed bariatric surgery. The present dissertation is made by two studies. The study 1 is an integrative review of the literature and has as answer the following guiding question, elaborated by the PICO strategy: What are the orientations in psychology (I)? Scopus, PubMED, PsycINFO and SciELO databases were consulted and withdrawals were published between January and 2012 and June 2017. Twenty-six articles were found, and the results pointed out the predominance of behavioral and / or cognitive behavioral information and some gaps in knowledge, such as the scarcity of national studies on the subject and the predominance of the female sample in the studies. Study 2, which deals with an exploratory, cross - sectional study supported by the qualitative methodology, had as objective to know the forms of obesity and the weight loss process in people who underwent bariatric surgery. They were included in the study of the clinical follow-up of the Ambulatory of Digestive System Surgery of HC-UFTM. For the sample size, the exhaustion criterion was used, in which all participants were submitted to the inclusion and exclusion criteria. Data were collected through a semi-structured interview. To analyze the data, an analysis of the data was used and it was done by the Social Representations of Serge Moscovici and with the support of the literature of the area. Sixteen participants, all women, were interviewed. What is a bariatric surgery is the question of everyday experiences, which face prejudices, stigma and difficulties with the fat body that they have; and different from this body, a lean and socially accepted body, is the object of desire and pursuit. The quest for weight loss appears in two ways: at first as a form of health reestablished, and there is no other way of reintegrating into society with the body within the pattern of beauty.